LOOKING INSIDE THE FOREST: FROM CLASSICAL GENOTYPING OF MYCOBACTERIUM TUBERCULOSIS TO WHOLE GENOME SEQUENCING IN HIGH MULTIDRUG RESISTANCE SETTINGS - J. Perdigão (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
.